FEMINIST CRITICAL DISCOURSE ANALYSIS OF FEMINIST VOICES AND RESISTANCE PRESENTED IN POETRY (Contemporary Journal of Social Science Review, 2026)
The current research work offers a multi-level Critical Discourse Analysis of the poems of two cross-border females, Kishwar Naheed from Pakistan and Maya Angelou from the United States, to analyse the use of language to highlight, critique, and challenge the linguistic practices that persistently uphold patriarchal power. Grass Is Really Like Me and Still I Rise are two poems analyzed using Feminist Critical Discourse Analysis at interconnected levels of linguistic use, as a framework developed by Lazar in 2005 and 2007. Lexical-level analysis provides insight into the use of metaphors, vocabulary, and repetition for ideological function, showing that language not only gives words meaning but also constructs gendered resistance. Syntactic-level analysis shows that transitivity patterns, grammatical modality, active and passive voice constructions, and syntactic parallelism are examined to reveal how sentence structure itself encodes agency, defiance, and the centering of female subjectivity. At the discourse level, the study highlights the intertextuality, subjev5 positioning, rhetorical progression, and interdiscursivity to illuminate how both poems operate as counternarratives within broader patriarchal and colonial discourse systems. The findings of the work show that language not only conveys meanings but also certain gender based concepts and ideologies. It shows that the feminist voices, themes, and issues faced by women are the same across cultures and borders. The application of Feminist Critical Discourse Analysis contributes by providing in-depth, multi-level analysis of the poems, rather than focusing on surface-level analysis, and by highlighting major feminist voices and patriarchy.